The Effect of Teaching and Supply Chain Management on Employees’ Skills in Small and Medium Sized Enterprises of Russia - Svetlana Fomina; Valeriya Sizikova; Yanina Shimanovskaya; Svetlana Kozlovskaya; Anastasia Karpunina (International Journal of Supply Chain Management, 2019)
Abstract- In recent years, there has been an increasing interest in the intervention of thinking skills. One of the main ways of guiding people's thinking about having a healthy and sensible life is to teach employees how to think correctly. Therefore, since the ultimate goal of education is learning, it is important to consider every factor that achieves this goal. Therefore, the main objective of the study was to investigate the effect of training and supply chain management on problem solving, critical thinking, creativity and social skills of employees. The statistical population of this research was all employees of the enterprises of Russia. A sample of this study included 40 employees who were selected through random sampling.